APLIKASI PENJADWALAN PAKAN AYAM DENGAN METODE SINGLE MOVING AVERAGE - Wahyu Nur Rochim; Dinny Wahyu Widarti (Dinamika Dotcom : Jurnal Pengembangan Manajemen Informatika dan Komputer, 2023)
Scheduling is a strategic part of the process of production planning and control, and also a plan of arrangement working order and allocation of resources, both time and facilities for each operation to be completed. One way fatherly determine scheduling is the single moving average. In PT. WONOKOYO JAYA CORPORINDO the process is done manually by the administrator by manual counting to determine the amount of feed to be submitted to Feedmill. In scheduling the manual feed is still only based on the guidelines, so that the feed management often occurs difference in the final accounting. Chicken weight less standardized so that the desired amount of egg production is far from the target firms. Calculations are still manually create a time-consuming job, so a lot of other work that eventually became tertnda process.Required application that is able to calculate the number of requests that feed directly without having to wait for the results of the manual counting by admin. These applications can help feed the scheduling process goes quickly. Implementation of the application is made with PHP, so to run it can use a browser application that has installed a computer.